Regulation Model of Southeast Sulawesi Provincial Government on Community Empowerment and Development Through Corporate Social and Responsibility (CSR) in Mining Sector - Hasriany Amin; Sutiyana Fachruddin (International Journal of Qualitative Research, 2022)
Southeast Sulawesi Province has abundant natural resources, especially the mining sector. This is proven by the number of mining business permits in Southeast Sulawesi, but they have not made a positive contribution to the community's economy. The implementation of Corporate Social and Responsibility (CSR) in Southeast Sulawesi is still partial in the form of local and stimulus. That it has not had a long-term impact. This study aims to describe the regional government regulation model of Southeast Sulawesi province in community empowerment and development through the CSR of mining sector companies. This study is a qualitative descriptive analysis and used purposive sampling to select informants at the Energy and Mineral Resources Ministry of Southeast Sulawesi. This study showed the Provincial Government of Southeast Sulawesi make a program framework (Blue Print) which became a mandatory document for implementing community empowerment by mining companies in Southeast Sulawesi. The community development and empowerment program is part of the vision and mission governor of Southeast Sulawesi as listed in the RPJMD 2018-2023. The PPM program aims to develop community life be better. They can be sovereign, safe in fields economy, hardiness food, education, health, environment, politics, have faith and piety.